Some new solutions of the (1+1)-dimensional PDE via the improved (G ′/ G)-expansion method - Naher, Hasibun; Abdullah, Farah Aini (© 2014 American Institute of Physics Inc., 2016)
This article was published in the Journal of Retailing [© 2014 Published by American Institute of Physics Inc.] and the definite version is available at: http://dx.doi.org/10.1063/1.4887630 The Journal's website is at: http://scitation.aip.org/content/aip/proceeding/aipcp/10.1063/1.4887630